COX‐2 Inhibition Antagonizes Intra‐Accumbens 2‐Arachidonoylglycerol–Mediated Reduction in Ethanol Self‐Administration in Rats. (3rd October 2020) - Pavon, Francisco J.; Polis, Ilham; Stouffer, David G.; Roberto, Marisa; Martin‐Fardon, Rémi; Rodriguez de Fonseca, Fernando; Parsons, Loren H.; Serrano, Antonia
Abstract : Background: Ethanol (EtOH) self‐administration is particularly sensitive to the modulation of CB1 signaling in the nucleus accumbens (NAc) shell, and EtOH consumption increases extracellular levels of the endogenous cannabinoid CB1 receptor agonist 2‐arachidonoyl glycerol (2‐AG) in this brain region. Stimulation of CB1 receptor with agonists increases EtOH consumption, suggesting that EtOH‐induced increases in 2‐AG might sustain motivation for EtOH intake. Methods: In order to further explore this hypothesis, we analyzed the alterations in operant EtOH self‐administration induced by intra‐NAc shell infusions of 2‐AG itself, the CB1 inverse agonist SR141716A, the 2‐AG clearance inhibitor URB602, anandamide, and the cyclooxygenase‐2 (COX‐2) inhibitor nimesulide. Results: Surprisingly, self‐administration of 10% EtOH was dose‐dependently reduced by either intra‐NAc shell SR141716A or 2‐AG infusions. Similar effects were found by intra‐NAc shell infusions of URB602, suggesting again a role for accumbal 2‐AG on the modulation of EtOH intake. Intra‐NAc shell anandamide did not alter EtOH self‐administration, pointing to a specific role for 2‐AG in the modulation of EtOH self‐administration. Finally, the inhibitory effect of intra‐NAc shell 2‐AG on EtOH intake was significantly reversed by pretreatment with nimesulide, suggesting that oxidative metabolites of 2‐AG might mediate these inhibitory effects on operant self‐administration. Conclusions: We propose that 2‐AG signaling in the NAc exerts an inhibitory influence on EtOH consumption through a non–CB1 receptor mechanism involving the COX‐2 pathway. Abstract : Ethanol self‐administration is particularly sensitive to manipulations of CB1 signaling in the nucleus accumbens shell (NAc) and ethanol consumption increases extracellular levels of the endogenous cannabinoid 2‐arachidonoylglycerol (2‐AG) in this brain region. We have shown that ethanol self‐administration was reduced by intra‐NAc infusions of 2‐AG, and this effect was significantly reversed by pretreatment with the COX‐2 inhibitor Nimesulide, suggesting that this inhibitory effect of 2‐AG may result from its metabolic conversion of prostaglandin‐E2 via COX‐2.